ALMA observations of CS in NGC 1068: chemistry and excitation. Issue 4 (2nd July 2020) - Scourfield, M; Viti, S; García-Burillo, S; Saintonge, A; Combes, F; Fuente, A; Henkel, C; Alonso-Herrero, A; Harada, N; Takano, S; Nakajima, T; Martín, S; et al.
ABSTRACT: We present results from Atacama Large Millimeter/submillimeter Array (ALMA) observations of CS from the nearby galaxy NGC 1068 (∼14 Mpc). This Seyfert 2 barred galaxy possesses a circumnuclear disc (CND, r ∼ 200 pc) and a starburst ring (SB ring, r ∼ 1.3 kpc). These high-resolution maps (∼0.5 arcsec, ∼35 pc) allow us to analyse specific sub-regions in the galaxy and investigate differences in line intensity ratios and physical conditions, particularly those between the CND and SB ring. Local thermodynamic equilibrium (LTE) analysis of the gas is used to calculate CS densities in each sub-region, followed by the non-LTE analysis conducted using the radiative transfer code radex to fit observations and constrain gas temperature, CS column density and hydrogen density. Finally, the chemical code uclchem is used to reconstruct the gas, allowing an insight into its origin and chemical history. The density of hydrogen in the CND is found to be ≥10 5 cm −2, although exact values vary, reaching 10 6 cm −2 at the active galactic nucleus. The conditions in the two arms of the SB ring appear similar to one another, though the density found (∼10 4 cm −2 ) is lower than in the CND. The temperature in the CND increases from east to west, and is also overall greater than found in the SB ring. These modelling methods indicate the requirement for multiphase gas components in order to fit the observed emission over the galaxy. A larger number of high-resolution transitions across the SLED may allow for further constraining of the conditions, particularly in the SB ring.